Structure-activity and selectivity relationships in heterogeneous catalysis : proceedings of the ACS Symposium on Structure-Activity Relationships in Heterogeneous Catalysis, Boston, MA, April 22-27, 1990 - ACS Symposium on Structure-Activity Relationships in Heterogeneous Catalysis (1990 : Boston, Mass.); Grasselli, Robert K., 1930-; Sleight, A. W.; ScienceDirect eBooks (Amsterdam ; New York : Elsevier, 1991)
Structure plays an important role in heterogeneous catalysis. It provides a framework for the arrangement and stragetic placement of key catalytic elements, hosting them in a prescribed manner so that their respective electronic properties can exhibit their desired catalytic functions and mutual interactions. Under reaction conditions these framework structures and their catalytic guests undergo dynamic processes becoming active participants of the overall catalytic process. They are not mere static geometric forms. The dynamics of catalytic structures are particularly vivid in selective oxidation catalysis where the lattice of a given catalytic solid partakes as a whole, not only its surface, in the redox processes of the reaction. The catalyst becomes actually a participating reagent. By proper choice of key catalytic elements and their host structures, preferred catalytic pathways can be selected over less desired ones. However, not only in selective redox catalysis does structure play an important role, its importance is also well documented, among others, in shape selective zeolite catalysis, enantioselective hydrogenation and hydrodesulfurization. The contributions presented in this book address the dynamic character of the solid state under catalytic reaction conditions. By relating structure to activity and selectivity in heterogeneous catalysis our understanding of such correlations has been significantly enhanced through the use of sophisticated spectroscopic means, surface science and modeling.
Chapter 5. Structure-activity relationships in the oxidation of alkylaromatics over metal oxidesChapter 6. Catalyst oxide support oxide interaction to prepare multifunctional oxidation catalysts; Chapter 7. Structural-sensitivity in propylene mild oxidation on new [100] oriented MoO3, catalysts; Chapter 8. A comparison between low and high temperature Bi2O3. MoO3 phases for 1-butene reactions; Chapter 9. Surface- and bulk-type cat.
Includes bibliographical references and index.
Print version record.
Elsevier
Keywords: Catalysts -- Structure-activity relationships -- Congresses; Heterogeneous catalysis -- Congresses; SCIENCE -- Chemistry -- Physical & Theoretical; Katalyse; Structuur-activiteit-relatie.; Catalise (fisico-quimica); Heterogeneous catalysis; Electronic books